Bioaugmented Phytoremediation: A Strategy for Reclamation of Diesel Oil-contaminated Soils - Chuluun, Buyan; Shah, Syed Haleem; Rhee, Jae-Seong (FRIENDS SCIENCE PUBL, 2014)
Oil spills to natural environment, either accidental or instinctive seepage, pose a long term threat to all kind of life. Efficient remediation techniques are still on the way of development. In the present study, phytoremediation process in combination with introduction of bacterial consortium in a diesel oil-contaminated soil was investigated in terms of removal of total petroleum hydrocarbons (TPH). A model soil spiked with 50 g diesel oil kg(-1) was incubated over a 90-day period at ambient condition in combination with perennial ryegrass (Lolium perenne L.) and with hydrocarbon (HC)-degrading bacterial consortium consisting ten strains isolated from petroleum contaminated soils. The average TPH removal efficiency of the bioaugmented phytoremedation was 57.3%, which was 7.3% more efficient than the phytoremediation alone and 5.3% more than the bioaugmentation alone. Mutual interactive effect of the perennial ryegrass and the inoculated bacterial consortium was expalined in terms of alteration in soil conditions, plant growth, bacterial population and diesel oil degradation in the soil. (C) 2014 Friends Science Publishers